I have a partner. (Journal of Parents and Teachers, 2014)
This article is the testimony of the companion of a person, who affirms that it is not true that the letter with blood enters, that to teach now is much more difficult than 30 years ago and that everything that is done is little if you want to offer an education quality.
Keywords: Testimony; education; teacher; partner.